Selective synaptic connections in the retinal pathway for night vision. Issue 1 (15th September 2017) - Beaudoin, Deborah L.; Kupershtok, Mania; Demb, Jonathan B.
Abstract: The mammalian retina encodes visual information in dim light using rod photoreceptors and a specialized circuit: rods→rod bipolar cells→AII amacrine cell. The AII amacrine cell uses sign‐conserving electrical synapses to modulate ON cone bipolar cell terminals and sign‐inverting chemical (glycinergic) synapses to modulate OFF cone cell bipolar terminals; these ON and OFF cone bipolar terminals then drive the output neurons, retinal ganglion cells (RGCs), following light increments and decrements, respectively. The AII amacrine cell also makes direct glycinergic synapses with certain RGCs, but it is not well established how many types receive this direct AII input. Here, we investigated functional AII amacrine→RGC synaptic connections in the retina of the guinea pig ( Cavia porcellus ) by recording inhibitory currents from RGCs in the presence of ionotropic glutamate receptor (iGluR) antagonists. This condition isolates a specific pathway through the AII amacrine cell that does not require iGluRs: cone→ON cone bipolar cell→AII amacrine cell→RGC. These recordings show that AII amacrine cells make direct synapses with OFF Alpha, OFF Delta and a smaller OFF transient RGC type that co‐stratifies with OFF Alpha cells. However, AII amacrine cells avoid making synapses with numerous RGC types that co‐stratify with the connected RGCs. Selective AII connections ensure that a privileged minority of RGC types receives direct input from the night‐vision pathway, independent from OFF bipolar cell activity. Furthermore, these results illustrate the specificity of retinal connections, which cannot be predicted solely by co‐stratification of dendrites and axons within the inner plexiform layer. Abstract : This study examined synaptic connections between retinal ganglion cells and the AII amacrine cell, which is a component of the night vision circuit in mammalian retina (rods → rod bipolar cells → AII amacrine cell). Using a physiological assay, combined with morphological analysis, we show that a direct inhibitory synapse from AII amacrine cells is limited to a privileged minority of ganglion cell types. More generally, co‐stratification did not reliably predict synaptic connection in the inner plexiform layer.